Analysis And Manufacturing Composite For Brake Shoes Of Motorcycle Honda Supra X 125 Using Fly Ash Coal And Magnesium Oxide With Epoxy Matrix - Arifin, Bukhori Isak, Dr. Supriyono, Wijianto, S.T., M.Eng.Sc (2013)
Brake is one component of a motor vehicle that serves to slow or stop, this is very important in supporting aspects of driving safety. The study aims to investigate the influence of use fly ash coal and Magnesium oxide (MgO) with epoxy matrix as a material brake shoes. The research was conducted in two phases, namely the field of testing and measuring brake wear in the lab. Metrology using a profile projector, in addition to the Brinell hardness testing is also performed to determine the hardness of each specimens of brake shoes before and after testing higher speeds with the same braking load time, braking distance and the wear rate also increased. From brinell hardness test results generated that hardness resulting from brake shoes variation has a value of 6.4 BHN and brake shoes variation 2 has a value of 14.8 BHN more great than brake shoes Honda Genuine Parts has a value of 12.3, while for Variation 3 has a value of 10.2 BHN and Variation 4 has value 8.9 BHN is smaller than Honda Genuine Parts brake shoes